PERPUSTAKAAN SIRING LAUT KOTABARU - Khalik Indra Parawangsa; Nurfansyah Nurfansyah (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2025)
This study examines the design of the Siring Laut Library in Kotabaru Regency, South Kalimantan, using a metaphorical architecture approach. Located in a strategic area of ​​Siring Laut which is the center of community activities, this library is designed to overcome the challenge of low interest in library visits in the area. With an area of ​​9,442.46 km² and a population of 290,142, Kotabaru presents significant opportunities for the development of innovative libraries that are inclusive and culturally diverse. The design method uses a metaphorical architecture approach to create buildings that are not only functional, but also have deep meaning for the local community. The main concepts include inclusivity, comfort, flexibility of space, and integration with the beauty of the surrounding nature. The building design is inspired by the shape of an open book, symbolizing the openness of knowledge. The design results include clear zoning, the use of modern technology to improve services, and the selection of materials that are appropriate to the conditions of the coastal environment. This library is expected to be an inspiring learning center, arousing a sense of pride in regional literacy, and becoming a catalyst for increasing the reading interest of the Kotabaru community.